Keep on Truckin' or Stay the Course? Exploring Grit Dimensions as Differential Predictors of Educational Achievement, Satisfaction, and Intentions. (August 2015) - Bowman, Nicholas A.; Hill, Patrick L.; Denson, Nida; Bronkema, Ryan
In an ongoing effort to identify predictors of educational success and achievement, grit has emerged as a seemingly useful disposition. Grit is conceived as the combination of perseverance of effort and consistency of interest over time, but the predictive utility of these two dimensions has rarely been explored separately, and the limited research available has considered a small number of outcomes. This article draws upon three samples at two universities to examine the relationships between grit dimensions and various student outcomes. Multiple regression results indicated that perseverance of effort predicted greater academic adjustment, college grade point average, college satisfaction, sense of belonging, faculty–student interactions, and intent to persist, while it was inversely related to intent to change majors. Consistency of interest was associated with less intent to change majors and careers, but it was not significantly associated with any other outcome in the expected direction when controlling for other variables.